The Relationship Between Learning Achievement and Family Environment on Job Readiness - Wiharto, Ega Sih Priyantika; Wahyudin, Agus; Santoso, Jarot Tri Bowo (Universitas Negeri Semarang, 2024)
Work readiness is the ability of individuals to be ready to work immediately without requiring long adjustments. The aim of this study was to analyze the effect of academic achievement and family environment on work readiness with self-efficacy as mediation and work motivation as moderation. The population of class XII students in the Field of Business and Management Skills at the Temanggung Regency Vocational High School in 2023/2024 is 744 students, samples taken by technique proportional random sampling obtained 88 respondent. Data collection techniques using a questionnaire. Data analysis techniques used descriptive statistical analysis, path analysis, and moderated regression analysis. The results showed that learning achievement did not affect work readiness, family environment and self-efficacy had an effect on work readiness, learning achievement had no effect on self-efficacy, family environment had an effect on self-efficacy, self-efficacy could not mediate the effect of learning achievement on work readiness, self-efficacy can mediate the influence of the family environment on work readiness, work motivation cannot strengthen the effect of learning achievement on work readiness, and work motivation can strengthen the influence of the family environment and self-efficacy on work readiness.